Influence of six different language learning strategies on the language learning experience of a group of low beginners of english whose main motivation is to help their school children at home - Sandí Bermúdez, Ivannia 1974- ([San José, Costa Rica], 2010)
The objective of this research study is to investigate the influence of teaching six language learning strategies to a group of seven beginning adult students at a public p1imary school in San José, who share one personal purpose: learn English to help their school children at home. The group received fourteen weeks of learning strategies training set into a great variety of classroom activities, while receiving English lessons. Questionnaires were administered to the students at the beginning and at the end of training. The analysis of the preliminary questionnaire provided comments, recommendations, and critical opinions to define students,. own learning strategies and enhance their communicative skills. The connotation of the research study is that language learning strategy preparation _should be integrated into the regular teaching program starting from the beginning levels to help students turn into more effective learners.
Práctica dirigida (licenciatura en lengua inglesa)--Universidad de Costa Rica. Facultad de Letras. Escuela de Lenguas Modernas, 2010.
Keywords: INGLES -- ESTUDIO Y ENSEÑANZA; LENGUAJE DE LOS NIÑOS -- TECNICAS